Valuating Indonesian Upstream Oil Management Scenario through System Dynamics Modelling - Fariza Aulia Putri; I Ketut Gunarta (Direktorat Riset dan Pengabdian Masyarakat (DRPM), ITS, 2017)
Under the existing regulation in Constitution Number 22 Year 2001 (UU No 22 Tahun 2001), Production Sharing Contract (PSC) continues to be the scenario in conducting oil and gas upstream mining activities as the previous regulation (UU No. 8 Tahun 1971). Because of the high costs and risks in upstream mining activities, the contractors are dominated by foreign companies, meanwhile National Oil Company (NOC) doesn’t act much. The domination of foreign contractor companies also warned Indonesia in several issues addressing to energy independence and energy security. Therefore, to achieve the goals of energy which is independence and security, there need to be a revision in upstream oil activities regulating scenario. The scenarios will be comparing the current scenario, which is PSC, with the “full concession” scenario for National Oil Company (NOC) in managing oil upstream mining activities. Both scenario will be modelled using System Dynamics methodology and assessed furthermore using financial valuation method of income approach. Under the 2 scenarios, the author will compare which scenario is better for upstream oil management in reaching the goals mentioned before and more profitable in financial aspect. From the simulation, it is gathered that concession scenario offers better option than PSC in reaching energy independence and energy security.